STUDI LITERATUR: PENGARUH KONDISI IKLIM DAN POLA PERILAKU PENGHUNI DAN IMPLIKASINYA TERHADAP PERANCANGAN SISTEM MEP PADA RUMAH TINGGAL DI WILAYAH SUBTROPIS - Fadilatul Anisa; Immanuel Surya Pratama; Dieksa Saputri Himawan; Nur Latifah Khomsiati; Tee Tze Kiong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the integration of climatic conditions, occupant behavior patterns, and their implications for the design of Mechanical, Electrical, and Plumbing (MEP) systems in residential buildings in the coastal subtropical region of Momochihama, Fukuoka. Using a descriptive qualitative literature review method, the research explores extreme environmental challenges such as high humidity and salt aerosol exposure. The findings indicate that the fluctuating subtropical climate necessitates the use of adaptive technologies such as Air-Source Heat Pumps and Energy Recovery Ventilation (ERV) for energy efficiency and humidity control. Furthermore, Japanese hygiene culture increases water and energy demands on plumbing and electrical systems. Design implications include the use of non-corrosive materials (PVC/HDPE) and stainless steel (SUS 316) to ensure material durability. System resilience is enhanced through the implementation of microgrids with battery energy storage and rainwater harvesting as strategies against extreme weather disasters. In conclusion, effective MEP design in subtropical coastal areas must synergize material resistance, understanding of local cultural behavior, and smart technology to achieve sustainable energy efficiency and thermal comfort.